Pengaruh Kualitas Pelaporan Keuangan, Debt Maturity Terhadap Efisiensi Investasi - Angelica Dipaulina; Sistya Rachmawati (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2023)
Purpose: This research aims to examine the influence of financial reporting quality and debit maturity on investment efficiency. Design/methodology/approach: This research is quantitative data. The population in this research is manufacturing companies in the raw goods sub sector in 2018-2022. Using the purposive sampling method, there were 10 companies as research samples. The analysis technique used to test the hypothesis is multiple regression analysis using eviews 9 software. Findings: Variable financial reporting quality is measured using Return on Assets (ROA). Variable Financial reporting quality is measured using Return on Assets (ROA). The debt maturity variable is measured using the Stdebt formula, while the investment efficiency variable is measured using sales growth. The type of data used is secondary data obtained from www.idx.co.id. The analysis method used is panel regression analysis. The results of this research indicate that the quality of financial reporting and debt maturity have a positive and insignificant effect on investment efficiency.